Turkey : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Turkey reviews a decline in private saving and adoption of a fiscal rule. As economic confidence has improved, capital inflows have surged while private saving has fallen. Together, these developments have produced current account deficits and a strong lira, raising concerns that Turkey may be exposed to sudden reversals in investor sentiment. A fiscal rule with appropriate mechanisms to monitor its compliance should deliver predictable policies, thus allowing further reductions in debt and risk premiums, thereby contributing to macroeconomic stability.